Strategi Pengembangan Pariwisata di Kabupaten Semarang - Dika Nurseptiani; M. Mustam (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The tourism sector in Semarang Regency is one contributor to PAD. Semarang regency with a conditions that have the potential of tourism and attraction of tourism, have opportunity to develop tourism into one of the leading sectors in the Semarang Regency. Tourism development strategy undertaken to develop tourism in Semarang regency. The purpose of this research is to analyze how the implementation of the tourism development strategy of Semarang Regency and identifies supporting and obstacles factors in its implementation. This study uses a descriptive qualitative research design with an informant from the Department of Youth, Sport and Tourism Semarang District, business and tourism services providers in Semarang, and tourist visitors. Results of the research tourism development strategy in Semarang Regency conducted through of the tourism destinations development, the tourism marketing development and development partnerships where tourism development needs to be focused is the development of tourism destinations by referring to the potential, the attractions and the condition of advice facilities each Tourism Destinations (DPD) Semarang regency so on get the focus on the development of DPD Lerep in Sub Ungaran West to serve as a tourist destination.